Bilan et perspectives sur la situation des compositrices au Québec : vers un décloisonnement des identités - Tremblay, Vicky (Les Cahiers de la Société québécoise de recherche en musique, 2017)
In the field of composition in Quebec, women composers are still less numerous than men composers. While the profession of composer has difficulty being recognized in Quebec society, women composers are twice as marginalized. Many of give evidence to the challenges they face when it comes to integrating into the musical community, and several musicologists have tried to better understand—and eventually solve—the problems specific to women in the field of composition.

Animating the Object: Marcelle Deschênes and acousmatic education in Quebec - Valiquet, Patrick (Organised Sound, 2017)
This article examines the early reception of Pierre Schaeffer’s theoretical work in Quebec through the teaching of Marcelle Deschênes, principal author of the first electroacoustic theory and ear training curricula at both Université Laval and Université de Montréal. An account of Deschênes’s educational career is provided, along with remarks on the contents of her early courses in Morpho-typology and her listening workshops for children, using newly excavated primary material from her private archives. While existing scholarship presumes that Schaefferian thinking arrived in Quebec with the ‘orthodox’ acousmatic approach of Francis Dhomont, this article asserts that a pluralist and multidisciplinary interpretation of Schaeffer’s work can be discerned which pre-dated Dhomont’s teaching and has had an equally lasting impact overall. A methodological argument is also made for including education and other forms of ‘reproductive labour’ in the history of electroacoustic music.